Factors Affecting the Corporate Governance Disclosure: An Analysis of Manufacturing Companies in Pakistan - Khan, Muhammad Faizan; Ahmad, Aqeel (The journal of contemporary issues in business and government, 2021)
In this manuscript, researcher examines the effect of different governance related variables on corporate governance disclosure in Pakistani manufacturing firms. The population for this particular study was Pakistan. Secondary sample was taken from Karachi Stock Exchange (KSE) indexed companies in Pakistan. There are total 903 companies listed in KSE in 2016 according to Pakistan Stock Exchange (Pakistan Stock Exchange, 2016). According to PSE; 903 companies were listed with KSE; out of 903, 129 were selected as part of sample for this particular study. The analyses are done through Logistic regression with the use of Stata software. A disclosure index consisting the four items which are adopt to serve as dependent variable. Independent variables are; Board Composition, Managerial Ownership and Audit firm status and there are two control variables Organization size and Organization age. Result of the study suggests that the Corporate Governance disclosure that is our dependent variable have positively affected by board composition and audit firm status. Managerial ownership have negative affect on corporate governance disclosure. In previous studies, managerial ownership also showed negative impact on corporate governance disclosure and here in this study impact was also same. The hypothesis related to managerial ownership is rejected in this study. Remaining hypothesis related to audit firm status and board composition are accepted. The findings reveals that all the independent variables except managerial ownership have not found positive relationship with the determinants of Corporate Governance disclosure.